A Work in Progress : Integrating Markets for Goods, Labor, and Capital in the East African Community - Alper, Emre (Departmental Papers; Departmental Paper ;, 2017)
This paper assesses the extent of economic and financial integration among the East African Community (EAC) along a number of dimensions and, where possible, whether integration has increased in the wake of the major regional integration policy milestones.